URGENSI MEMBACA DENGAN IQ, EQ DAN SQ UNTUK PEMBANGUNAN MANUSIA DALAM PENDIDIKAN ISLAM - Rohmat, Rohmat (Millah: Journal of Religious Studies, 2010)
The article elaborates the urgent of reading as one of methods for human development in Islamic Education. Reading is the first revelation received by Rasulullah. Therefore, it is a crucial aspect in the process of human empowerment. However, the problem is that reading activities are still assumed as brain activities which are a part of Intelligence Quotient/IQ. In fact, reading can really empower human being if it is involving Emotional Quotient/EQ, and Spiritual Quotient/SQ. The article provides a conclusion that human empowerment requires reading process that engages Intelligence Quotient/IQ, Emotional Quotient/EQ, and Spiritual Quotient/SQ.